Critical thinking, social education and the curriculum: foregrounding a social and relational epistemology. Issue 1 (2nd January 2015) - Lim, Leonel
Abstract : In this article, I examine the extent to which, given how critical thinking has been most commonly conceptualised and taught in schools, the subject indeed develops modes of thinking, relating and reasoning that allow individuals to collectively work towards the appreciation and solution of social problems. In the first section, I outline a number of perspectives among social studies researchers and educators that demonstrate the importance of developing critical thinking capacities in students. This is followed by, in the next section, a close examination of two widely popular approaches through which critical thinking is taught – one in the general school curriculum and the other within social studies lessons. I argue that in their current forms and for a number of reasons these understandings of critical thinking fall short of developing the social and relational dimensions of thinking that are more than a little necessary in fulfilling the raison d'etre of the subject. Towards this end, the final section presents a social epistemological framework for the teaching of critical thinking in the school curriculum, highlights a number of principles of its application and provides some examples of its use in classrooms.